Dukungan Keluarga Pada Psikologis Penderita Hypertensi Dapat Mencegah Peningkatan Tekanan Darah Dan Stroke Di Puskesmas Padang Tahun 2024 - Eka Seba Marta; Erni Musmiler (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2024)
Hypertension in West Sumatra is around 22.6%, in Padang City in 2021 the prevalence is 51.36%. Based on data from health centers in Padang City, hypertension in Alai health centers was 63.1%. The aim of the research was to determine whether family support for the psychology of hypertension sufferers can prevent increased blood pressure and stroke at Padang health centers in 2024. This type of research is analytical with a cross sectional design. The population is hypertension sufferers. The population is 309 respondents. Accidental sampling technique totaling 76 people. Chi-square analysis CI 64.5% (α = 0.00). The research was conducted March 15 – June 25 2024. Keywords: Family Support; Stroke;